Intraoperative uterine packing with abdominal mops as adjunct to management of postpartum haemorrhage in a low resource setting. (2021)
Background: Postpartum haemorrhage (PPH) remains a leading contributory factor to maternal morbidity and mortality especially among women undergoing caesarean deliveries. Despite concerted efforts being made towards prevention, recurrent limiting factors in low-resource settings warrant the adoption of mechanisms that would further assist in combating the scourge. This study reviewed the outcome of intra-operative uterine packing of bleeding uteri in limiting blood loss from PPH. Methods: We reviewed the hospital records of patients who had postpartum haemorrhage over a period of five months retrospectively and present the outcome of 17 consecutive cases which were managed with intrauterine packing with abdominal mop as an adjunct measure. Structured proforma was used to obtain information on age, parity, socioeconomic status, mode of delivery, indications for surgery and history of intrauterine packing from the hospital records while data analysis was done using the statistical package for social sciences, SPSS, version 23.0. Results: Most common cause of intraoperative PPH was uterine atony, 13 (76.5%), and the mean blood loss was 1841.2±1165.4mL. Mean duration of intrauterine packing was 36.7±15.0 hours and average number of days on admission was 4.0±2.5.An average of 2 abdominal mops was used per packing and most procedures were performed by the medical officers (10, 58.8%). Overall, there was no case of maternal mortality among the patients managed and no abnormality was detected on follow up at 6 weeks. Conclusion: Uterine gauze packing is effective in reducing blood loss from intra-operative PPH in low resource-settings. It, therefore, deserves reconsideration as an addition to the armamentarium of available resources for reducing mortalities from PPH in developing countries.